KOMUNIKASI POLITIK: PENYAMPAIAN PESAN DAN PEMILIHAN MEDIA OLEH BAKAL CALON PRESIDEN DALAM PEMILU TAHUN 2024 - Alif, M. Ismail (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
Political communication cannot be separated from the role of the mass media in conveying messages to target audiences in particular and the public in general. Especially now that politics is present everywhere thanks to media networks that have real-time broadcasting capabilities. In political communication, political figures are often or packaged in political advertisements or various styles of political communication that must follow the liberalization of the media system which is more capital-oriented (money oriented) through political campaigns. From here arises media relations with political parties and actors and some others also influence the role of owners of media capital who are also politicians or leaders of political parties as seen on Metro TV. The results of this study show that the relationship between the media and politics is found in the news on the Prospective Candidates for the 2024 Presidential Election in the news on Metro TV. Thanks to media networks that have real-time broadcasting capabilities, new media have sprung up, both in the form of dare media (on-line) and social media, both of which are inseparable from being used as political communication channels to shape imagery, both positive and negative, from political actors. As a result, the social media arena is often used as a buzzer for news that is the mainstream of the media so that it can strengthen the formation of public opinion. This study also found a correlation between political communication conveyed through mainstream media and social media. This can be seen from a number of issues that are used in political communication as an effort to image the Presidential Candidate through conversations on social media in which many buzzers and loyalists from political actors are mobilized